Preparation and Energy Storage Performance of Perovskite Luminescent Materials by an Electrochemiluminescence Method - Dan Cheng; Zhaohai Yang; Yilan Liang (Adsorption Science & Technology, 2022)
In recent years, metal halide perovskites have become attractive photosensitive materials due to their excellent optoelectronic properties. Due to its good characteristics, perovskites are used in solar photovoltaic power generation, light-emitting diodes, photodetectors, photocatalysis, and sensors and many other fields. Considering the wide application of perovskites and the study of potential bifunctional devices, the application of perovskites in energy storage devices is relatively small, and a small number of studies focus on organic-inorganic hybrid lead-halide perovskites. However, the related energy storage research on all-inorganic lead-halide perovskites with better stability, which has also been widely concerned, is very scarce. And nontoxic all-inorganic nonperovskite has zero research in energy storage. Based on the above situation, this paper selects the lead-free perovskite Cs2AgSbCl6, and two lead halide perovskites with different dimensions, -0-dimensional Cs4PbBr6 and 3-dimensional CsPbBr3, these three all-inorganic perovskites. It was for electrochemical performance testing.